A Preliminary Experiment of Non-Catalytic Transesterification: Thermal Analysis of Palm Oil and Biodiesel at Different Ratio - Ong, Mei Yin; Salman, Bello; SAL, Nor-Insyirah; Hussein, Refal; Nomanbhay, Saifuddin (International Journal of Engineering and Technology, 2018)
Currently, the biodiesel production technology is moving toward the trend of non-catalytic reaction under subcritical condition as the conventional non-catalytic transesterification requires high energy input and high production cost. Hence, non-catalytic biodiesel production under subcritical condition using microwave energy is proposed. Before that, thermogravimetric analysis (TGA) was conducted to characterize the biodiesel feedstock and determine the suitable experimental temperature range for the proposed method. Besides, the thermal behavior of the palm oil and biodiesel at different stages of reaction was also investigated. The results showed that the palm oil and biodiesel were started to degrade from 335ºC and 160ºC respectively. However, the degradation point of palm oil was higher than the supercritical temperature of DMC. So, external energy is needed to bring down the operating condition, such as microwave energy as it has potential to reduce the activation energy. To further eliminate the problem of biodiesel thermal degradation during the transesterification process, the suggested experimental temperature range is within 80ºC to 180ºC, which is from the temperature lower than the boiling point of DMC (<90ºC) to the temperature slightly higher than the biodiesel thermal degradation point. Furthermore, DSC result indicated that palm oil requires 518.35kJ/mol to decompose.